Evaluation of three broth disk methods for testing the susceptibility of anaerobic bacteria to imipenem. - Shungu, D L (1985)
Imipenem is a member of a new class of highly potent beta-lactam antibiotics, carbapenems, with an antibacterial spectrum that includes nearly all currently known aerobic and anaerobic bacterial species of clinical significance. Although relatively stable in most standard laboratory media used for antimicrobial susceptibility testing, imipenem undergoes rapid inactivation in thioglycolate broth, a recommended medium for susceptibility testing of anaerobic bacteria by the broth disk method. In the current study, a panel of 36 anaerobic bacteria consisting of 28 clinical isolates and eight quality control strains was used to determine the suitability and accuracy of the broth disk methods with brain heart infusion, Schaedler, and anaerobic broths, in comparison to the reference agar dilution method, for the anaerobic susceptibility testing of imipenem. To achieve single test concentrations of approximately 8, 16, and 64 micrograms/ml for imipenem, cefoxitin, and piperacillin, respectively, which correspond to the MIC breakpoints of the test drugs, four 10-microgram imipenem disks, three 30-microgram cefoxitin disks, and three 100-microgram piperacillin disks were used in 5 ml of broth. The correlation between the reference agar dilution method and each of the three broth disk elution procedures evaluated was excellent, for imipenem (100% agreement) and somewhat less so for cefoxitin and piperacillin. Therefore, brain heart infusion, Schaedler, and anaerobic broths, but not thioglycolate broth, are suitable for anaerobic susceptibility testing of imipenem by the disk elution method.